Histology and Geochemistry of Allosaurus (Dinosauria: Theropoda) From the Cleveland-Lloyd Dinosaur Quarry (Late Jurassic, Utah): Paleobiological Implications - Ferrante, Christophe; Cavin, Lionel; Vennemann, Torsten; Martini, Rossana (Frontiers in Earth Science, 2021)
The Late Jurassic Allosaurus is one of the better-studied dinosaurs. A histological and geochemical study of a tibia and a femur of A. fragilis recovered in the Upper Jurassic Cleveland-Lloyd Dinosaur Quarry, Utah, USA has been done in order to address growth characteristics of this species. The two bones, probably belonging to separate individuals, are among the largest known for this species, which make them suitable to address such issues. The inclusion of our data on femur growth markings in the previously published data reflects a range of growth variability rather than two distinct growth strategies. The tibia has a well-developed external fundamental system indicating somatic maturity achievement. Using a quantitative method of superimposition to retrocalculate missing lines of arrested growth, the tibia appears to correspond to an individual that reached its skeletal maturity at 22 years and died at approximately 26 years. In the tibia, the concentration of zinc, a potential biomarker associated with bone formation, displays a higher concentration in zones of rapid growth compared to annuli. There is no direct relationship between the values of δ18Op and the lines of arrested growth distribution. The absence of relations between the histological organization and an enrichment in REE of the bone, indicates that the variations of δ18Op likely represent a diagenetic process rather than a primordial, biologic composition. However, the geochemical composition of the bones is not homogeneous along the sections, indicating that the signal variations have not been completely erased by diagenesis.